Recognition and Determination of Customary Forests by Indigenous Peoples in the West Sumatra Province - Syofiarti (Ekasakti Journal of Law and Justice, 2023)
Forests are a natural resource used by communities around the forest to support their lives, including the Customary Law Community or Masyarakat Hukum Adat (MHA). However, various tenurial conflicts are often encountered in forest utilization, such as claims over forest areas. The basis of the problem, which then causes the community around the forest, often conflicts with government policies. However, the issuance of Constitutional Court Decision No.35/PUU-X/2012 provides a form of recognition to MHA in managing forests and determines customary forests as the forest within the territory of MHA. This research will focus on two issues: first, how is the recognition and determination of customary forest by MHA after the presence of the Constitutional Court Decision No.35/PUU-X/2012. Second, how are efforts to recognize and determine customary forests through social forestry schemes in the Province of West Sumatra. To answer the focus of the study, this study used normative juridical research methods with descriptive research specifications and analyzed them through library research. The conclusion of this study is obtained.Forests are a natural resource used by communities around the forest to support their lives, including the Customary Law Community or Masyarakat Hukum Adat (MHA). However, various tenurial conflicts are often encountered in forest utilization, such as claims over forest areas. The basis of the problem, which then causes the community around the forest, often conflicts with government policies. However, the issuance of Constitutional Court Decision No.35/PUU-X/2012 provides a form of recognition to MHA in managing forests and determines customary forests as the forest within the territory of MHA. This research will focus on two issues: first, how is the recognition and determination of customary forest by MHA after the presence of the Constitutional Court Decision No.35/PUU-X/2012. Second, how are efforts to recognize and determine customary forests through social forestry schemes in the Province of West Sumatra. To answer the focus of the study, this study used normative juridical research methods with descriptive research specifications and analyzed them through library research. The conclusion of this study is obtained.